Performance improvement for IEEE 802.15.4 CSMA/CA scheme in large‐scale wireless multi‐hop sensor networks. Issue 2 (1st June 2013) - Zhu, Jianping; Tao, Zhengsu; Lv, Chunfeng
Abstract : The hidden‐terminal problem and routing establishment or maintenance bring about a tremendous amount of energy consumption in multi‐hop wireless sensor networks (WSNs). In this study, the authors propose a carrier sense multiple access with collision avoidance (CSMA/CA) scheme MultiCSMA for multi‐hop WSNs adopting two strategies which refer to a novel hidden‐terminal list algorithm to avoid the impact of hidden terminals and a parallel access scheme to dispense with taking the routing overhead into account. The accurate statistical performance metrics of throughput and delay of unsaturated, unacknowledged IEEE 802.15.4 beacon enabled networks for one‐hop and two‐hop scenarios are predicted based on Markov models adopting these two improved strategies, in which nodes are assumed to locate randomly over a circle plane according to Poisson distribution. Comprehensive simulations demonstrate that the analysis results match well with the simulation results, and delay performance of the authors schemes is superior to those of other schemes, whereas throughput is superior to others for relative higher node density.